Using stable isotopes to measure the dietary responses of Costa Rican forest birds to agricultural countryside - Şekercioğlu, Çağan H.; Fullwood, Melissa J.; Cerling, Thure E.; Brenes, Federico Oviedo; Daily, Gretchen C.; Ehrlich, Paul R.; Chamberlain, Page; Newsome, Seth D. (Frontiers in Ecology and Evolution, 2023)
How human modification of native habitats changes the feeding patterns and nutritional ecology of tropical birds is critical to conserving avian biodiversity, but tropical bird diets are laborious to investigate using the traditional methods of diet analysis. Stable isotope analysis provides a cost-effective and efficient proxy to identify general foraging patterns, especially when dietary shifts spanning multiple trophic levels have occurred due to ecosystem disturbance or transformation. To characterize the diets of forest bird species that persist in tropical agricultural countryside, we compared feather carbon (13C) and nitrogen (15N) isotope values of four species caught and radio-tracked in a 270 hectare forest reserve, smaller forest remnants (including mature forest, secondary forest, and riparian strips), and coffee plantations in mid-elevation (ca. 800-1400 m) southern Costa Rica. Bird habitat choice had a significant effect on diet composition as revealed by 13C and 15N values. Three of the four species studied showed evidence of significantly reduced consumption of invertebrates in coffee plantations, with the isotope values of two species (Tangara icterocephala and Turdus assimilis) indicating, by comparison, nearly a doubling of invertebrate consumption in forest remnants. Our results suggest that coffee plantations are deficient in invertebrates preferred by forest generalist birds that forage in both native forest remnants and coffee plantations. In this region, typical of mountainous American tropics, small forest remnants and a larger forest reserve provide critical dietary resources for native forest birds that utilize the agricultural countryside.